Induksi Tunas In Vitro Bawang Putih pada Umur Simpan Umbi dengan Suhu Rendah dan Komposisi ZPT Berbeda - Elara Resigia; Netti Herawati; Nilla Kristina (JURNAL GALUNG TROPIKA, 2021)
Garlic is one of the agricultural commodities needed by people in Indonesia. The productivity of local garlic produced is still low due to the limited availability of seed tubers and the non-uniform quality of tubers. Production and quality of garlic seed bulbs can be increased through the shelf life of bulbs at low temperatures by tissue culture techniques. This study aimed to determine the effect of the shelf life of tubers at low temperatures and the composition of growth regulators on garlic shoot induction. The design used was a randomized block design for two treatment factors and 15 replications. The first factor was the shelf life of tubers at low temperatures, which consisted of 4 treatments, namely 0, 10, 20, and 30 days. The second factor is the composition of growth regulators consisting of: 2.0 ppm Kinetin + 0.4 ppm 2.4-D; 2.0 ppm NAA + 2.0 ppm BAP; 0.5 ppm NAA + 2.0 ppm 2ip; and 0.2 ppm NAA + 2.25 ppm BAP. The results obtained from this study were that the shelf life of 0 days with the composition of ZPT 2 ppm NAA + 2 ppm BAP, and shelf life of 10 days 0.5 ppm NAA + 2.25 ppm BAP affected shoot emergence time, the number of explants sprouted, and percentage of explants sprouted.